South Florida Tropical Fruit Grower Perspectives: Water Conservation Management Practices - Kati W. Migliaccio; Jonathan H. Crane; Edward Evans; Bruce Schaffer; Yuncong Li; Rafael Muñoz-Carpena (EDIS)
ABE-368, a 5-page fact sheet by Kati W. Migliaccio, Jonathan H. Crane, Edward Evans, Bruce Schaffer, Yuncong Li, and Rafael Muñoz-Carpena, presents the results of a survey designed to assess changing views of tropical fruit producers in Miami-Dade County regarding water quantity and quality management practices. Published by the UF Department of Agricultural and Biological Engineering, July 2006.